Managing Innovation in Japan The Role Institutions Play in Helping or Hindering how Companies Develop Technology - Watanabe, Chihiro (Springer Berlin Heidelberg : Imprint: Springer, 2009)
Why do some country's hi-tech firms innovate better than others? Why did hi-tech firms from the United States outperform such Japanese companies in the 1990s? Through a wealth of empirical evidence, the book compares the development trajectory of manufacturing technology and information technology both between Japanese companies and between companies based in the US, Europe, Australia, India and China. This book shows that institutional systems such as culture, tradition, consumers and local business practices play key roles in how companies develop technology. These factors also influence the very characteristics of the products that the hi-tech firms produce. With a number of case studies the author demonstrates how the most successful and innovative companies recognize these roles and incorporate them into their practices.